2020
DOI: 10.36740/wlek202001130
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Immunoglobulin Spectra of Tissue Extracts From Tonsils of Children With Hypertrophy and Chronic Tonsillitis

Abstract: The aim: To compare the content of α and γ–interferons, interleukins 1β ,4, 10, IgA, IgG, as well as the level of the general forms of immune complexes in tissue extracts from tonsils of children with hypertrophy and chronic tonsillitis. Materials and methods: We studied tonsils of 25 children aged 5-12 years with hypertrophy of palatine tonsils (HPT) and with chronic tonsillitis (CT). The content of α and γ – interferons, interleukins 1β, 4, 10, IgA, IgG in tonsil extract was determined by immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The existence of Th1-type cytokines as IFN-γ and TNF-α is found to be higher in recurrent tonsillitis group when it is compared with hypertrophic tonsil group by Todorović et al 1 Bredun et al also found that the content of proinflammatory-IL-1β is significantly higher in chronic tonsillitis. 11 We did not find any differences related expression IL-1, also TNF-α, IL-15, and IL-6.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The existence of Th1-type cytokines as IFN-γ and TNF-α is found to be higher in recurrent tonsillitis group when it is compared with hypertrophic tonsil group by Todorović et al 1 Bredun et al also found that the content of proinflammatory-IL-1β is significantly higher in chronic tonsillitis. 11 We did not find any differences related expression IL-1, also TNF-α, IL-15, and IL-6.…”
Section: Discussioncontrasting
confidence: 52%
“…Some authors believe that hypertrophy of palatine tonsils and tonsillitis significantly differs in nonspecific immunity and inflammation. 11 This study compared the expression of interleukin (IL)-1 α and β, IL-6, IL-8, IL-15 and tumor necrosis factor alpha (TNF-α) cytokines between recurrent tonsillitis and hypertrophic tonsil tissues.…”
mentioning
confidence: 99%
“…Besides, tonsils of Waldeyer's ring can form both, primary and secondary levels of protection, as practically all types of interleukins, interferons, lymphotoxin, tumour necrosis factor, platelet-derived growth factor are separated from the tonsils' tissues. There was also determined a range of cytokines that have as a factor of inhibiting microphages and leucocytes -MIF and LIF, transfer-factor, that can delay hypersensitivity to antigens and enhance antigen response [15].…”
mentioning
confidence: 99%